Impact of sugammadex on postoperative pneumonia and COPD exacerbations in COPD patients - Fu-Chi Kang; Ting-Sian Yu; Chih-Wei Hsu; Yi-Chen Lai; Shu-Wei Liao; Kuo-Chuan Hung (Medicine, 2026)
Patients with chronic obstructive pulmonary disease (COPD) have an elevated risk of postoperative pulmonary complications. This study investigated whether sugammadex use was associated with a reduced risk of postoperative pneumonia and COPD exacerbations compared to neostigmine in this high-risk population. This retrospective cohort study utilized the TriNetX database to identify COPD patients undergoing elective surgery under general anesthesia between 2015 and 2024. Patients receiving rocuronium with sugammadex reversal were compared to those receiving neostigmine reversal using 1:1 propensity score matching. The primary outcome was 30-day postoperative pneumonia. Secondary outcomes included risks of COPD exacerbations, mortality, and intensive care unit (ICU) admission. After matching, 34,031 patients were analyzed per group. Sugammadex was associated with a reduced 30-day pneumonia incidence (1.8% vs 2.1%; hazard ratio [HR] 0.84, 95% confidence interval [CI] 0.75–0.94, P = .002) but increased ICU admissions (2.3% vs 1.9%; HR 1.22, 95% CI 1.10–1.36, P < .001). No significant differences were observed in COPD exacerbations (1.1% vs 1.3%; HR 0.90, 95% CI 0.79–1.04, P = .146) or mortality (0.89% vs 0.79%; HR 1.13, 95% CI 0.96–1.33, P = .147). Sensitivity and subgroup analyses revealed that benefits were more pronounced in academic centers (HR 0.64, 95% CI 0.57–0.73, P < .001) and elderly patients (HR 0.76, 95% CI 0.68–0.84, P < .001). Effects disappeared during the 30 to 90 day follow-up. Sugammadex use in COPD patients was associated with reduced 30-day postoperative pneumonia, particularly in elderly patients and academic settings. However, this benefit did not translate to fewer COPD exacerbations and was temporally limited. The increased ICU admissions likely reflect selection bias rather than causation.